2019
DOI: 10.1111/jpc.14711
|View full text |Cite
|
Sign up to set email alerts
|

Time spent watching television impacts on body mass index in youth with obesity, but only in those with shortest sleep duration

Abstract: Aim:To determine the interplay between sleep and sedentary behaviours on body mass index (BMI) in children with obesity. Methods: Cross-sectional study of 343 children with obesity aged 4-17 years, from a tertiary care weight management clinic in Melbourne, Victoria, Australia. Multifaceted data relating to activity and sleep from child and parent questionnaires analysed with anthropometric data collected during routine clinical care. Associations between sleep duration and activity measures were examined via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…This contradiction is not surprising. Although concerns about mental health stressfulness of media are debatable, either due to cultural differences [ 25 ], wide misconceptions about the definition of stress [ 18 ], or individual reasons for use [ 6 , 14 - 16 , 36 ], deleterious physical health effects of excessive screen time are quantifiable [ 4 , 5 , 41 , 42 ]. One out of four respondents were very worried about the physical health risks of increased screen time, but only 1 out of 7 were concerned about the mental health risks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contradiction is not surprising. Although concerns about mental health stressfulness of media are debatable, either due to cultural differences [ 25 ], wide misconceptions about the definition of stress [ 18 ], or individual reasons for use [ 6 , 14 - 16 , 36 ], deleterious physical health effects of excessive screen time are quantifiable [ 4 , 5 , 41 , 42 ]. One out of four respondents were very worried about the physical health risks of increased screen time, but only 1 out of 7 were concerned about the mental health risks.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing concern about the potential adverse effects of excessive screen time on emotional and physical health. To name a few harms, there is stress caused by an abundance of catastrophic news [ 2 ]; increased sedentary behavior and obesity [ 3 , 4 ]; sleep disorders [ 5 ]; and addiction to social media [ 6 ], computer games [ 7 ], online gambling [ 8 ], etc. Nevertheless, the debate about the directional relationship between stress and compulsive screen use is nuanced.…”
Section: Introductionmentioning
confidence: 99%
“…Many literature studies extensively identified that either irregular physical exercise or physical inactiveness [7,10,14,15,26,30], watching television or prolonged screen time [27,30], short sleep duration or shift work [15,24,30], stress, obesogenic environment (urbanization and industrialization) [31], smoking [10], and frequent use of a taxi for transportation [10,32] were determinant factors for overweight/obesity.…”
Section: Behavioral Factors (Feeding Habit and Life Style)mentioning
confidence: 99%
“…Watching electronic screens for more than 2 hours increases the development of obesity because during simple observation, the brain does not utilize glucose and as a result, the metabolism of carbohydrate to glycogen and fat increased consistently [27,30]. e correlation between stress and the development of obesity has different scientific perspectives.…”
Section: Behavioral Factors (Feeding Habit and Life Style)mentioning
confidence: 99%
“…This contradiction is not surprising. Although concerns about mental health stressfulness of media are debatable, either due to cultural differences [25], wide misconceptions about the definition of stress [18], or individual reasons for use [6,[14][15][16]36], deleterious physical health effects of excessive screen time are quantifiable [4,5,41,42]. One out of four respondents were very worried about the physical health risks of increased screen time, but only 1 out of 7 were concerned about the mental health risks.…”
Section: The Main Worry About Excessive Screen Time Is Physical Stressmentioning
confidence: 99%